EFFECTS OF OVER−DAY AND OVERNIGHT FASTING ON THE HEMATOLOGICAL, BIOCHEMICAL AND OXIDATIVE PROFILE OF HEALTHY DOGS - Souza, Wennely Karoline Costa; Mendonça, Mariana Orlandini; de Oliveira, Tainara Martins; Gonçalves, Geovanna Santos [UNESP]; Vieira, Susana Eduardo [UNESP]; Monzani, Guilherme Stuqui; de Oliveira, Paula Lima; Bosculo, Maria Rachel Melo; Floriano, Beatriz Perez; Almeida, Breno Fernando Martins (Universidade Federal do Paraná, 2022)
The influence of the circadian rhythm on canine laboratory parameters is yet to be elucidated. This study aimed to investigate possible fluctuations that occur on laboratory tests of healthy dogs following overnight and over−day fasting. For this purpose, 20 adult clinically healthy dogs were enrolled in the study. Venous blood samples were obtained 7:00 am (ONF, overnight fasting) and at 7:00 pm (ODF, over−day fasting) at the same day, following a 12−hour period of respectively overnight and over−day fasting for hematological, biochemical and oxidative stress assessment. The erythrogram showed significant reduction of red blood cells, hemoglobin, hematocrit and mean corpuscular volume (MCV) measured by the cell counter following ODF. The only change seen on the leukogram was a lower lymphocyte count following ODF. No significant changes were found on platelet count, although ODF was associated with decreased mean platelet volume (MPV) and total plasma protein (TPP). ODF caused a significant reduction of total cholesterol, ALP, phosphate and triglycerides. On oxidative stress parameters, ODF reduced total oxidant capacity (TOC) and increased lipid peroxidation. In conclusion, the time of fasting can partly influence hematological, biochemical and oxidative stress parameters in dogs significantly, which warrants standardization of fasting period prior to laboratory tests in dogs, especially during research.
(Efeito do período de jejum diurno e noturno sobre os parâmetros hematológicos, bioquímicos e de estresse oxidativo de cães saudáveis)
Keywords: Canine; Circadian cycle; Laboratory evaluation